"We make them give more": Women's roles in the exchange and redistribution of food across ethnic boundaries. Issue 3 (1st October 2016) - Corr, Rachel
ABSTRACT: Andean indigenous people have historically engaged in multiple strategies in order to procure a variety of foods for themselves and their families. Here I focus on the persistence of seasonal barter among people in Tungurahua province, Ecuador, as I observed it in 2011 and 2015. The exchanges I witnessed, combined with food-centered oral histories, show women's resourcefulness in acquiring food from different ecological zones and redistributing it to children, husbands, and kin. The people involved in these exchanges are from different ethnic backgrounds and have no social relationship or long-term obligations to one another. Food was the medium through which they interacted and food formed the topic of conversation between strangers who had a mutual interest in the direct exchange of one food for another. Through their activities, the women created a temporary, currency-free zone in semi-public space and contributed to their families' subsistence.